Neutrophils Contribute to Severity of Tuberculosis Pathology and Recovery From Lung Damage Pre- and Posttreatment. (24th August 2021) - Nwongbouwoh Muefong, Caleb; Owolabi, Olumuyiwa; Donkor, Simon; Charalambous, Salome; Bakuli, Abhishek; Rachow, Andrea; Geldmacher, Christof; Sutherland, Jayne S
Abstract: Background: Despite microbiological cure, about 50% of tuberculosis (TB) patients have poor lung recovery. Neutrophils are associated with lung pathology; however, CD16/CD62L-defined subsets have not been studied in TB. Using flow cytometry, we monitored frequencies, phenotype, and function of neutrophils following stimulation with Mycobacterium tuberculosis ( Mtb ) whole cell lysate (WCL) and ESAT-6/CFP-10 fusion protein (EC) in relation to lung pathology. Methods: Fresh blood from 42 adult, human immunodeficiency virus (HIV)–negative TB patients were analyzed pre- and post-therapy, with disease severity determined using chest radiography and bacterial load. Flow cytometry was used to monitor frequencies, phenotype, and function (generation of reactive oxygen species [ROS], together with CD11b, tumor necrosis factor, and interleukin 10 [IL-10] expression) of neutrophils following 2-hour stimulation with Mtb -specific antigens. Results: Total neutrophils decreased by post-treatment compared to baseline ( P = .0059); however, CD16 br CD62L br (segmented) neutrophils increased ( P = .0031) and CD16 dim CD62L br (banded) neutrophils decreased ( P = .038). Banded neutrophils were lower in patients with severe lung damage at baseline ( P = .035). Following WCL stimulation, ROS from segmented neutrophils was higher in patients with low Mtb loads even after adjusting for sex ( P = .038), whereas IL-10–expressing CD16 dim CD62L lo cells were higher in patients with mild damage ( P = .0397) at baseline. Conclusions: High ROS generation, low levels of banded neutrophils, and high levels of IL-10–expressing CD16 dim CD62L lo neutrophils are associated with reduced lung pathology at diagnosis. Hence, neutrophils are potential early indicators of TB severity and promising targets for TB host-directed therapy. Abstract : Neutrophil-mediated (proportions of functional protective subtypes and reactive oxygen species generation capacity) tuberculosis susceptibility constitutes a strong scientific premise for future mechanistic and clinical studies targeting immunosuppressive host-directed therapies for tuberculosis disease progression and severity.